Angiotensin-(1-7) Prevents Lipopolysaccharide-Induced Autophagy Via the Mas Receptor in Skeletal Muscle - Cabello-Verrugio, C; Tacchi, F; Abrigo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Skeletal muscle atrophy, which occurs in lipopolysaccharide (LPS)-induced sepsis, causes a severe muscle function reduction. The increased autophagy contributes to sepsis-induced skeletal muscle atrophy in a model of LPS injection, increasing LC3II/LC3I ratio, autophagy flux, and autophagosomes. Angiotensin-(1-7) (Ang-(1-7)) has anti-atrophic effects via the Mas receptor in skeletal muscle. However, the impact of Ang-(1-7) on LPS-induced autophagy is unknown. In this study, we determined the effect of Ang-(1-7) on sepsis-induced muscle autophagy. C57BL6 wild-type (WT) mice and mice lacking the Mas receptor (KO Mas) were injected with LPS together with the systemic administration of Ang-(1-7) to determine autophagy in skeletal muscle. We also evaluated autophagy and p38 and c-Jun N-terminal kinase (JNK)activation. Our results show that Ang-(1-7) prevents LPS-induced autophagy in the diaphragm, tibialis anterior, and gastrocnemius of WT mice, which is demonstrated by a decrease in the LC3II/LC3I ratio and mRNA levels of lc3b and ctsl. This effect was lost in KO Mas mice, suggesting the role of the Mas receptor. The results in C2C12 cells show that Ang-(1-7) reduces several LPS-dependent effects, such as autophagy (LC3II/LC3I ratio, autophagic flux, and autophagosomes), activation of p38 and JNK, B-cell lymphoma-2 (BCL2) phosphorylation, and disassembly of the Beclin1/BCL2 complex. In conclusion, Ang-(1-7)/Mas receptor reduces LPS-induced autophagy in skeletal muscle. In vitro assays indicate that Ang-(1-7) prevents LPS-induced autophagy and modifies the MAPK signaling and the disassembly of a complex involved at the beginning of autophagy. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.